Intention Awareness: A Vision Declaration and Illustrating Scenarios - Kymalainen, Tiina; Plomp, Johan; Heikkila, Paivi; Ailisto, Heikki (2014 International Conference on Intelligent Environments, 2014)
This is a position paper that introduces intention awareness (IA) as a counterfactual approach for designing IA technologies. The approach distinguishes human intention as a premise for developing intention-aware systems. Intention-aware technologies utilise information about the user's intentions to improve the services that are provided by the environment. The paper will initially define intention awareness as a concept, and subsequently introduce four scenarios that illustrate the approach.